Border Experiences in Europe Everyday Life - Working Life - Communication - Languages - Nienaber, Birte (Border Studies. Cultures, Spaces, Orders, 2019)
For a decade now, borders in Europe have been back on the political agenda. Border research has responded and is breaking new ground in thinking about and exploring borders. This book follows this development and strengthens a perspective that is interested in life realities and that focuses on everyday cultural experiences of borders. The authors reconstruct such experiences in the context of different forms of migration and mobility as well as language contact situations and are sensitive to the freedom of the participants. In this way, they empirically identify everyday cultural usage or appropriation strategies of borders as vastly different experiences of borders. The readers of this volume will gain insights into current developments in border research and liefe realities in Europe where borders are (made) relevant. With contributions by Christian Wille, Birte Nienaber, Carsten Yndigegn, Isabelle Pigeron-Piroth, Rachid Belkacem, Ursula Roos, Elisabeth Boesen, Ariela House, Ignacy Jóźwiak, Corinne Martin, Erika Kalocsányiová, Xosé-Afonso Álvarez, Konstanze Jungbluth, Florian Dost, Nicole Richter, Dominik Gerst Seit einem Jahrzehnt stehen Grenzen in Europa wieder auf der politischen Agenda. Die Grenzforschung hat darauf reagiert und schlägt neue Wege ein, um Grenzen zu denken und zu untersuchen. Das Buch folgt dieser Entwicklung und macht eine Perspektive stark, die sich für Lebenswirklichkeiten interessiert und die alltagskulturelle Erfahrung der Grenze in den Blick rückt. Die Autor_innen rekonstruieren solche Erfahrungen im Kontext verschiedener Migrations- und Mobilitätsformen sowie Sprachkontaktsituationen und sind sensibel für die Gestaltungsspielräume der Akteure. Auf diese Weise werden alltagskulturelle Gebrauchs- bzw. Aneignungsstrategien von Grenzen als höchst unterschiedliche Erfahrungen der Grenze empirisch herausgearbeitet. Die Leser des Bands bekommen Einblicke in aktuelle Entwicklungen der Grenzforschung und in Lebenswirklichkeiten in Europa, in denen Grenzen relevant (gemacht) werden. Mit Beiträgen von Christian Wille, Birte Nienaber, Carsten Yndigegn, Isabelle Pigeron-Piroth, Rachid Belkacem, Ursula Roos, Elisabeth Boesen, Ariela House, Ignacy Jóźwiak, Corinne Martin, Erika Kalocsányiová, Xosé-Afonso Álvarez, Konstanze Jungbluth, Florian Dost, Nicole Richter, Dominik Gerst